Aplicación de las Normas de Control Interno en el Departamento Financiero del Gobierno Autónomo Descentralizado Municipal del Cantón Urdaneta - De La Ese Mayorga, Noemí Lidia (2018)
The Municipal Autonomous Decentralized Government of Urdaneta is a public entity with administrative autonomy in charge of planning and managing the use of public resources, in order to generate citizen satisfaction through the provision of of quality services and the execution of works that benefit the Canton. The internal control standards are guidelines that allow the evaluation of the performance of activities developed in the institution framed in the components of internal control, these standards allow us to obtain efficiency and effectiveness in the development of functions that each of the public servants perform, through the application of measures to counteract the control deficiency. The objective of this case study is to make known the processes that are carried out in the financial department of Urdaneta's GADM, contrasting it with what it establishes Internal Control Standards issued by the Comptroller General of the State, with the purpose to provide a mechanism to mitigate the inherent risk and control that can be evidence in the execution of processes. In this case study we will analyze THE APPLICATION OF THE RULES OF INTERNAL CONTROL IN THE FINANCIAL DEPARTMENT AT GADM DE URDANETA, applying the explanatory method under the management research sub-line financial and social commitment, resorting to the use of interviews with staff to know the problems that affect this department; analyzing the causes that lead to application of internal control in each of the processes carried out by the GADM, taking advantage of the resources provided by the state to achieve the objectives institutional